INOVASI APLIKASI ENVIRONMENTAL MATHEMATICS PADA SMARTPHONE SEBAGAI MEDIA INTERAKTIF PEMBELAJARAN MATEMATIKA BERBASIS LINGKUNGAN - Yunni Arnidha; Shalsa Mahani Yusron (Jurnal Muara Pendidikan, 2023)
This research is development research (R&D) which refers to the ADDIE model. Development procedures include Analysis, Design, Development, Implementation, and Evaluation. The results of this research product are in the form of an android application based on environmental mathematics to improve understanding of learning mathematics based on the environment. The application is accompanied by attractive images, sounds, animations, and text narration. The results of the study show that the android application for learning environmental mathematics is feasible and effective in learning data collection, as seen from the average pretest and posttest scores carried out by fifth-grade students at SDN 1 Talang Padang. The average value obtained during the pretest was 41.57 while the average value obtained during the posttest was 82.10. Based on the Mann-Whitney test with a sample of two different schools, the resulting data shows a significant difference between the learning outcomes of schools that use the Android application media and those that are not treated, as seen from the posttest average score of SDN 1 Talang Padang of 82.10. While the average posttest score of SDN 1 Banding Agung is 66.31.